Monetary policy, macroprudential policy, and bank risk-taking behaviour in the Indonesian banking industry - Cep Jandi Anwar; Nicholas Okot; Indra Suhendra; Dwi Indriyani; Ferry Jie (Journal of Applied Economics, 2024)
There is a growing consensus on the translation of monetary policy actions into changes in credit demand on account of changes in interest rates. The study investigates monetary policy, macroprudential policy, bank-specific and macroeconomic determinants of bank risk-taking from 2010-2022 in Indonesia. The study aims to address a gap in the literature because most previous studies have focused on advanced markets. First, three POLS and fixed effect models are estimated. However, the Durbin Wu-Hausman test indicated endogeneity issues with the estimated models. The second stage uses a system GMM estimation to investigate the impact of central bank rates and macroprudential policy on bank risk-taking. Dynamic-GMM estimations find that, partially the central bank rate and macroprudential policy have a positive impact on bank Z-Score. Furthermore, when central bank rate and macroprudential policy are included in a model, we still find a positive impact of both policies on bank Z-Score.
Keywords: 330; bank risk-taking; Central bank rate; macroprudential policy; Z-Score